Beispiel Nr: 06
$c=\log_{b} a \Leftrightarrow b^{c}=a \quad \log_c a+\log_c b = \log_c (a \cdot b) \quad \log_c a-\log_c b =\log _c\frac{a}{b} \quad log_c a^n=n\log_c a \\ \\ \textbf{Gegeben:} \\ {a=2 \qquad b=4 \qquad c=2 \qquad n=4}\\ \\ \textbf{Rechnung:} \\ \log_{4} 2 =\frac{1}{2} \Leftrightarrow 4^{\frac{1}{2}}=2 \\ \log_2 2+\log_2 4 = \log_2 (2 \cdot 4)= \log_2 (2 \cdot 4)=3 \\ \log_2 2-\log_2 4 =\log_2\frac{2}{4}= -1\\ \log_2 2^4=4\log_2 2 = 4\\ \log_4 2=\dfrac{\log_2 2}{\log_2 4}=\frac{1}{2} $